A Large Retrospective Study of 12714 Cases of LEEP Conization Focusing on Cervical Cancer That Colposcopy-Directed Biopsy Failed to Detect. (30th April 2018) - Cong, Qing; Song, Yu; Wang, Qing; Zhang, Hongwei; Gao, Shujun; Du, Ming; Xie, Feng; Dong, Jing; Feng, Hua; Diao, Wenjing; Zhu, Caiying; Sui, Long
Abstract : Punch biopsy is important in the diagnosis of cervical cancer. However, it may fail to detect early cervical cancers. A retrospective study was performed in the largest academic women's hospital in China to demonstrate cervical cancer that colposcopy-directed biopsy failed to detect. Methods . Patients who were diagnosed with high-grade squamous intraepithelial lesion (HSIL), adenocarcinoma in situ (AIS), and persistent low-grade squamous intraepithelial lesion (LSIL) via colposcopy-directed biopsy and had further undergone loop electrosurgical excision procedure (LEEP) conization were included. These procedures were performed at Obstetrics and Gynecology Hospital of Fudan University from July 1, 2013, to December 31, 2016. In total, 5.98% (760/12714) of patients who underwent conization were diagnosed with invasive cervical cancer. Persistent LSIL (0.24%), HSIL (6.37%), and AIS (24.31%) were detected cancer by conization. Histological subtypes included squamous cell carcinoma (92.0%), adenocarcinoma (5.1%), adenosquamous carcinoma (1.8%), adenoid basal type carcinoma (0.9%), and small cell neuroendocrine carcinoma (0.1%). Cytology reports consisted of HSIL (45.4%), atypical squamous cells of undetermined significance (ASC-US) (16.1%), and LSIL (11.6%), and atypical squamous cells cannot exclude HSIL (ASC-H) (9.3%), squamous cell carcinoma (0.9%), AGC (atypical glandular cells, 0.9%), AIS (0.4%), and NILM (negative for intraepithelial lesion or malignancy, 15.4%). The sensitivity of high-risk human papillomavirus (hrHPV) screening (96.4%) was significantly higher than that of cytology (84.6%)( P < 0.01 ), with sensitivity of cotesting at 99.8% and a ratio of double-negative results at 0.2%. The sensitivity of cytology and hrHPV screening of different cervical cancer histologic subtypes was also demonstrated. In this large retrospective study, we systematically reported the cytology, hrHPV, pathology, and stages of cervical cancer that colposcopy-directed biopsy failed to detect.